Active Role of a Color Indicator in Buoyancy-Driven Instabilities of Chemical Fronts - Almarcha, C. (2010)
Chemical reactions are able to trigger hydrodynamic flows by changing the density of the solutions across reactive interfaces. In this work, an experimental study of the buoyancy-driven hydrodynamic instabilities that can occur when two miscible reactive solutions of an acid−base system are put in contact in the gravity field shows that the patterns observed and the instabilities taking place strongly depend on the presence of a color indicator. A reaction−diffusion−convection model explains how the color indicator can modify the instability scenarios by affecting the density of the solutions and allows one to numerically recover the observed experimental patterns. The present work clearly demonstrates that color indicators should therefore be used with caution in experimental works devoted to analyze reaction−diffusion−convection patterns and instabilities.